Environmental influences on childhood asthma—The effect of diet and microbiome on asthma. Issue 12 (7th December 2022) - Lunjani, Nonhlanhla; Walsh, Laura J.; Venter, Carina; Power, Matthew; MacSharry, John; Murphy, Desmond M.; O'Mahony, Liam
Abstract: Early life dietary patterns and timely maturation of mucosa‐associated microbial communities are important factors influencing immune development and for establishing robust immune tolerance networks. Microbial fermentation of dietary components in vivo generates a vast array of molecules, some of which are integral components of the molecular circuitry that regulates immune and metabolic functions. These in turn protect against aberrant inflammatory processes and promote effector immune responses that quickly eliminate pathogens. Multiple studies suggest that changes in dietary habits, altered microbiome composition, and microbial metabolism are associated with asthma risk and disease severity. While it remains unclear whether these microbiome alterations are a cause or consequence of dysregulated immune responses, there is significant potential for using diet in targeted manipulations of the gut microbiome and its metabolic functions in promoting immune health. In this article, we will summarize our knowledge to date on the role of dietary patterns and microbiome activities on immune responses within the airways. Given the malleability of the human microbiome, its integration into the immune system, and its responsiveness to diet, this makes it a highly attractive target for therapeutic and nutritional intervention in children with asthma.